Characterization of brown film formed by Lentinula edodes. Issue 2 (February 2020) - Yan, Dong; Liu, Yu; Rong, Chengbo; Song, Shuang; Zhao, Shuang; Qin, Luming; Wang, Shouxian; Gao, Qi
Abstract: Lentinula edodes is a widely-produced mushroom in China that forms a brown film via pigment accumulation on mature mycelial surfaces to ensure high-quantity and high-quality fruiting body formation. Here, ultraviolet–visible, infrared spectra, and elemental analyses predicted that the pigment in the brown film was melanin. Electron microscopy revealed the size, morphological characteristics, accumulation, and morphogenesis of electron-dense material, which were similar to those of melanin, as well as subcellular structural changes during brown film formation. The electron-dense material appeared as granules, vesicles, and polymers. The accumulation of electron-dense materials on the cell wall was followed plasmolysis, plasma membrane disruption, electron-dense material accumulation in the interstitial space, and gradual accumulation on the outer cell wall. Dolipore septa degradation and morphogenetic cell death occurred during browning. In the final stage of browning, the dolipore septum disappeared and the cell was nearly empty. This study provides a cytological foundation for evaluating the regulation of brown film formation in L. edodes.